2020
DOI: 10.1186/s12872-020-01463-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma lipoprotein-associated phospholipase A2 levels are associated with coronary slow flow

Abstract: Objective Coronary slow flow (CSF) is characterized by delayed opacification of distal epicardial coronary arteries without significant coronary stenosis. In addition, The changes of lipoprotein-associated phospholipase A2 (Lp-PLA2) as a significant predictive factor for CSF remain controversial. The study aims to investigate the association between plasma Lp-PLA2 and CSF. Methods In this retrospective study, 170 consecutive patients who underwent coronary angiography were enrolled in Beijing Anzhen Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Pekdemir et al [ 19 ] reported diffuse intimal thickening and calcifications along epicardial arteries during coronary angiography examinations of patients with CSF. Ding et al [ 20 ] reported that lipoprotein-associated phospholipase A2, which plays a role in inflammation and atherosclerosis in the vessel walls, was significantly and independently associated with the presence of CSF. Considering the data obtained from these studies, it may be reasonable to conclude that diffuse coronary atherosclerosis plays a role in the etiopathogenesis of CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Pekdemir et al [ 19 ] reported diffuse intimal thickening and calcifications along epicardial arteries during coronary angiography examinations of patients with CSF. Ding et al [ 20 ] reported that lipoprotein-associated phospholipase A2, which plays a role in inflammation and atherosclerosis in the vessel walls, was significantly and independently associated with the presence of CSF. Considering the data obtained from these studies, it may be reasonable to conclude that diffuse coronary atherosclerosis plays a role in the etiopathogenesis of CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-activating factor can promote platelet aggregation in the body, chemotaxis of neutrophils and mononuclear macrophages, and release of inflammatory mediators such as leukotriene, participate in the inflammatory response of the body, and promote the occurrence and progression of atherosclerotic plaques. Platelet-activating factor can be hydrolyzed by LP-PLA2 and then lose its biological activity, reduce the inflammatory response of the body, and have antiatherosclerosis and anti-inflammatory functions [ 25 , 26 ]. However, most clinical studies show that it mainly participates in the body's inflammatory response and plays a role in promoting the body's inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms have been proposed, such as the endothelial dysfunction theory 28 , early atherosclerosis 29 , microvascular disease 5 , 30 , platelet dysfunction 31 , changes in hemorheology 32 , 33 , and oxidative stress and local/systemic inflammatory response 3 5 . Recently, some studies have indicated that lipoprotein-associated phospholipase A2 34 , plasma choline 35 , or serum salusin beta level 36 could be a predictive or diagnostic biomarker for CSF.…”
Section: Discussionmentioning
confidence: 99%